Phakomatosis pigmentovascularis type-IIIb with Klippel-Trenaunay-Weber syndrome. - Borlu, M.; Uksal, U.; Utas, S.; Ferahbas, A. (European Journal of Pediatric Dermatology, 2007)
Phakomatosis pigmentovascularis is characterized by the simultaneous occurrence of vascular and melanocytic or epidermal nevi in the same patient with or without systemic involvement. We present a patient with phakomatosis pigmentovascularis type IIIb accompanied with nevus flammeus and mottled hypermelanic nevus and associated with Klippel-Trenaunay-Weber syndrome. The pathogenesis of phakomatosis pigmentovascularis is still controversial. It has been proposed that the combination of vascular and pigmentary anomalies arises because of a genetic concept called the twin-spot phenomenon. Phakomatosis pigmentovascularis type IIIb is very rare and our case is the first one from Turkey.